SOME RESULTS OF REFORM OF THE SOCIAL SPHERE OF THE RUSSIAN FEDERATION - R. Zh. Sirazhdinov (Publishing House of the State University of Management, 2019)
Over the past 20 years significant changes in all aspects of the social sphere are carried out in Russia. At the same time, the population does not always understand, what caused them and does not always support them. The changes in approaches to the concept of social development in Russia have been examined in the article. The necessary conditions for the development of the social sphere, based on its own resources and capabilities, have been considered. The main factors, influencing efficiency of functioning of all social sphere, in particular balance and security of resources of separate decisions, have been analyzed.